Предмет:
МатематикаАвтор:
bongowp3lОтвет:
1 + 3√3
Пошаговое объяснение:
√(22+6√(3+√(13+√(48)))) = √(22+6√(3+√(13+4√3))) = √(22+6√(3+√(1+2√3)²)) =
= √(22+6√(3+1+2√3)) = √(22+6√(4+2√3)) = √(22+6√(1+√3)²) =
=√(22+6(1+√3)) = √(22+6+6√3) = √(28 + 6√3) = √(1+3√3)² = 1 + 3√3
Автор:
dannyДобавить свой ответ
Предмет:
МатематикаАвтор:
jerónimoОтветов:
Смотреть
Предмет:
ХимияАвтор:
maggiedpziОтветов:
Смотреть
Предмет:
МатематикаАвтор:
gilliand8ffОтветов:
Смотреть
Предмет:
Русский языкАвтор:
paceОтветов:
Смотреть